A scalable system for the fast production of RNA with homogeneous terminal ends. Issue 1 (31st December 2022) - Chen, Yuchen; Cheng, Yan; Lin, Jinzhong
ABSTRACT: In vitro transcription (IVT) using T7 RNA polymerase has become the most common method to synthesize RNAs for use in basic research and pharmaceutical applications. To solve the heterogeneity issue associated with the system, cis-acting ribozymes have been exploited to direct co-transcriptional processing to yield target RNAs with precisely defined ends. However, traditionally used ribozymes have many limitations, such as low efficiency and special sequence requirements of target RNAs. In addition, the introduction of ribozymes in IVT complicates the downstream purification of target RNAs. Here we describe a new cassette of engineered ribozymes (HHV-Kt and Twister-Kt) that can work in concert to produce RNA with defined 5' and 3' ends. The pair of ribozymes displayed reliably high activity when working with RNA of various lengths and structures. The engineered ribozymes also carry a K-turn RNA motif that enables fast post-IVT clearance of cleaved ribozymes and uncleaved precursors using K-turn affinity resins. Finally, we demonstrated the scalability of our system for the rapid production of large quantities of homogeneous RNA samples.